SOCIAL CAPITAL SUPPORT ON PASTORAL COMPETENCE IN THE PERFORMANCE OF THE CHURCH - Kres Ari Kawalo; Adriana Madya Marampa (Proceeding of The International Conference on Economics and Business, 2022)
Competence is an essential thing in the development and growth of an organization. The church is an organizational unit that requires pastoral competence. Pastoral competence needs to be developed in improving church performance. A pastor must be able to have the social capital to improve church performance. The population of this study was pastors throughout Indonesia. The sample in this study were pastors of the Pentecostal Church in Indonesia (GPdI) spread across several regions in Indonesia as many as 42 pastors. The method in this study uses quantitative methods with SEM-PLS. The results showed that the competence of the pastor affects social capital. It can be seen from the analysis test showing that the variable considered to be significant if the P-value is smaller than the predetermined significant value (0.000 < 0.05), thus hypothesis H1 is accepted. The results of the study show that there is a relationship between social capital and church performance. It can be shown by the results of the SEM-PLS analysis showing that the P-value is smaller than the predetermined significant value (0.000 < 0.05); thus, hypothesis H2 is accepted. The results showed that there was a relationship between social capital and church performance. The results showed that there was a relationship between social capital and performance. It shows that the P-value is smaller than the predetermined significant value (0.000 < 0.05). Thus the hypothesis H3 is accepted. The originality of this study is that the competence of a pastor affects social capital, using several new dimensions that previous researchers have not studied